Improving the Arabic Writing Skills of Students through the Application of Contextual Learning Methods at Dayah Irsyadul Abidin Qurani - Rahmat Sapaat Siregar (MANDAILING GLOBAL EDUKASIA, 2025)
To achieve this goal, this study tries to test the effectiveness of the use of contextual teaching approaches on the Arabic writing skills of students in Dayah Irsyadul Abidin Qurani at the Tsanawiyah level. This study uses a quasi-experimental approach with 15 students in grades 7 and 8 as subjects. Data were obtained from writing tests (pre and post-treatment), observation of the learning process, interviews with teachers and students. The assessment instrument uses the rubric of assessing writing skills in terms of vocabulary, sentence structure, and paragraph coherence. The analysis technique used is qualitative descriptive analysis. The results of the pre-test showed that many students had a weak writing style, lacked diversity, paragraphs were lower than 36 and incoherent, the bandwidth to sentences about pronoun structures was 2 and 4, essential omission was responded to 10, and substantive paraphrasing played a role of 98. After four contextual sessions of nine sessions that addressed descriptive, narrative, dialogue, and personal letters, the average length of the cooperative paragraph had increased. Students do it easily and smoothly in an average of 25–40 words to 60–80 words. In each paragraph that is composed, a paragraph to write as an idea is flowed in writing. The vocabulary used to start using and connect is also relevant words in everyday conversation, with the right expression temperature for the child and personal experience. With this pedagogical certificate, students are able to write well after having experience in writing.